Pengaruh Promotion, Product Quality dan Fear of Missing Out (FOMO) terhadap Purchase Intention Jersey ERSPO Tim Nasional Sepak Bola Indonesia - Dhaniyanto, Naufal (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of promotion, product quality, and fear of missing out (FOMO) on the purchase intention of ERSPO Indonesian National Football Team jerseys. The study uses a quantitative descriptive approach with primary data collection through an online questionnaire of 200 respondents who are active fans of the national team on social media and have experienced FOMO. The data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS. The results showed that promotion had a positive and significant effect on purchase intention, while product quality and FOMO had no significant effect. These findings indicate that the effectiveness of promotional strategies plays a dominant role in increasing consumer purchase intention for ERSPO jerseys compared to product quality and the psychological factor of FOMO. Therefore, companies are advised to focus their marketing strategies on strengthening promotional activities that are relevant and attractive to consumers.